2018
DOI: 10.18520/cs/v114/i10/2106-2115
|View full text |Cite
|
Sign up to set email alerts
|

Paddy Cultivation during Early Holocene:Evidence from Diatoms in Lahuradewa Lake Sediments, Ganga Plain

Abstract: Lahuradewa lake deposits, adjacent to the Lahuradewa archaeological site were rich in diatoms, going back to about 10 kyrs. The diatoms are grouped into four categories, namely, planktic, benthic, paddy field and anthropogenic-influenced. The variation in planktic and benthic forms reflects changes in the water budget of the lake in response to the change in rainfall, viz. more planktic in humid phases and less planktic in dry phases. These changes correspond to the changes identified by other proxies, namely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Saxena et al (2006) suggested the appearance of cultivated rice phytotlith at 8300 cal yr BP, indicating agararian practice at the Lahurdeva Lake region, central Ganga Plain. Thakur et al (2018) further substantiated the agricultural activities on the basis of diatoms with reference to the paddy field cultivation ca. 8 ka.…”
Section: Agricultural Practices and Other Anthropogenic Activities In...mentioning
confidence: 91%
“…Saxena et al (2006) suggested the appearance of cultivated rice phytotlith at 8300 cal yr BP, indicating agararian practice at the Lahurdeva Lake region, central Ganga Plain. Thakur et al (2018) further substantiated the agricultural activities on the basis of diatoms with reference to the paddy field cultivation ca. 8 ka.…”
Section: Agricultural Practices and Other Anthropogenic Activities In...mentioning
confidence: 91%
“…The stability in rice production achieved is evidently due to the cultivation of so many preferred old or aged genotypes in addition to hundreds of commercially notified cultivars in fragmented landholdings in monsoon-dependent farmers' fields in India. About 9000 years BP, the human population at the Lahuradewa archaeological site of the Indo-Gangetic plains used the lake margin to cultivate rice (Thakur et al 2018). India is a home for over 20,000 traditional landraces and 15,000 Indian cultivars are given to IRRI's germplasm bank (IRRI 1991).…”
Section: Considering Farmers' Preferences In Bs Seed Productionmentioning
confidence: 99%
“…Past climate variability and its various manifestations both in terms of magnitude and periodicity can provide clues for plausible future changes along with anthropogenic forcings. Until now several sedimentary archives have been studied from the Ganga Plain (Misra et al, 2020; Saxena and Trivedi, 2017; Thakur et al, 2018; Tripathi et al, 2017). However, there is still a paucity of climatic data for the Late-Holocene (Meghalayan Age- 4.2 ka to present) in the river interfluve region.…”
Section: Introductionmentioning
confidence: 99%